Microwave-assisted synthesis of icosahedral nickel nanocrystals - HOLMES, JUSTIN DEREK; DONEGAN, JOHN FRANCIS (My University, 2011)
Nickel nanocrystals with icosahedral morphologies have been successfully synthesised using a microwave-assisted irradiation method. Nickel acetylacetonate was used as the metal precursor, while sodium formate and trioctylphosphine oxide were employed as the reducing agent and capping ligands, respectively. The nanocrystals, with a mean diameter of 237 ? 43 nm, exhibited enhanced ferromagnetic behaviour at room temperature compared to bulk nickel, with coercivities of up to 164 Oe and saturation magnetisation values of up to 46 emu g?1, due to their icosahedral morphologies.
PUBLISHED
Keywords: Condensed matter physics; Nickel nanocrystals